Financing renewable electricity in the resource-rich countries of the Middle East and North Africa: A review - Krupa, J; Poudineh, R (Oxford Institute for Energy Studies, 2017)
Renewables in the resource-rich countries of the Middle East and North Africa (MENA) are inconsequential contributors to regional total primary energy supply, but recent project developments and overt support from a range of influential regional actors suggest a general trend towards a more environmentally sustainable electricity supply. This trend is driven just as much by economics as other factors, as rapidly falling renewable energy capital costs are complementing favourable policy environments, technical suitability, and concerns around the impacts of anthropogenic climate change. Finance is an especially important consideration in this transition, yet it receives insufficient coverage. This paper seeks to remedy this deficiency of academic inquiry. At the root of our inquiry lies a simple pair of questions: what makes a project financeable, and what can the resource-rich nations of the region do to create vibrant clean electricity financing markets for renewables? We outline the factors that affect the financeability of projects, review the latest developments in renewable energy finance in the region, and present policy recommendations going forward.